ANALISIS PENGARUH REMUNERASI DAN EMPLOYEE ENGAGEMENT TERHADAP KINERJA PEGAWAI LEMBAGA SANDI NEGARA - Dwi Indah Retnoningtyas (Universitas Mercu Buana, 2014)
Abstract: The research aims are to analyze influance of remuneration and employee engagement on employee’s performance in Lembaga Sandi Negara. Data was collected through questioner and it was implemented to Department of Public Functional in Lembaga Sandi Negara. This research sampling technique used quantitative approach and used validity test by product moment and alfa cronbach reliability test. Analysis result demonstrate that remuneration and employee engagement has positive significant toward to employee’s performance in Lembaga Sandi Negara.Keyword: Remuneration, Employee Engagement, Employee Performance